FEATURES OF PROFESSIONAL-ORIENTED TEACHING IN INFORMATION TECHNOLOGIES (European Journal of Pedagogical Initiatives and Educational Practices, 2025)
This article analyzes the specific features of vocational education and the advantages of using information technologies. The study examines the possibilities of improving the quality of education through vocational education.